Analgesia before Performing Subarachnoid Block in the Sitting Position in Patients with Proximal Femoral Fracture: A Comparison between Fascia Iliaca Block and Femoral Nerve Block - Ghimire, A.; Bhattarai, B .; Koirala, S.; Subedi, A. (Kathmandu University Medical Journal, 2017)
Background Positioning for subarachnoid block (SAB) in patients with femoral fracture is painful and may remain suboptimal requiring use of large doses of opioids. These patients generally being elderly with multiple comorbidities and frailty are likely to have many undesirable effects of opioids including respiratory depression and confusion.Objective The objective was to compare the feasibility and effectiveness of fascia iliaca compartment block (FICB) and femoral nerve block (FNB) in reducing pain associated with positioning for subarachnoid block in patients undergoing proximal femoral fracture fixation procedures.Method Group FICB patients (n=15) received fascia iliaca block with 30 ml of 1.5% lignocaine with adrenaline and group FNB patients (n=15) received femoral nerve block with 15 ml of 1.5% lignocaine with adrenaline. After the study blocks, patients were kept on supine position for at least 20 minutes before shifting them to the operation theatre. Pain was assessed by using visual analog scale values before the block and during the position for subarachnoid block. Time to perform subarachnoid block, quality of positioning and acceptance was recorded.Result Visual analog scale values during positioning for SAB were lower in FIB group than in FNB (1.0±1.1 versus 2.1±0.8; P